1995
DOI: 10.1002/eji.1830251037
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐4 inhibits χ light chain expression and NFχB activation but not IχBα degradation in 70Z/3 murine pre‐B cells

Abstract: The murine pre-B cell line 70Z/3 responds to lipopolysaccharide by up-regulating the surface expression of kappa (kappa) light chain through activation of the transcription factor NF kappa B. Interleukin-4 (IL-4), a T cell cytokine, is a known inhibitor of some LPS-mediated events. We investigated whether IL-4 could inhibit the up-regulation of kappa light chain and activation of NF kappa B by LPS in 70Z/3. IL-4 partially inhibited both the LPS-induced expression of kappa light chain and also the activation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…The antibody recognizing Ser 32-36 phosphorylated I B␣ was purchased from Cell Signaling Technology (Hitchin, UK). Nuclear extracts (10 g) were examined for NF-B DNA-binding activity using EMSA, as previously described (47).…”
Section: Methodsmentioning
confidence: 99%
“…The antibody recognizing Ser 32-36 phosphorylated I B␣ was purchased from Cell Signaling Technology (Hitchin, UK). Nuclear extracts (10 g) were examined for NF-B DNA-binding activity using EMSA, as previously described (47).…”
Section: Methodsmentioning
confidence: 99%
“…Cytosolic and nuclear extracts of DCs were prepared as described (43). Cytosolic proteins were analyzed by Western blotting for I B␣, and nuclear extracts (10 g) for NF-B DNA-binding activity were analyzed by EMSA.…”
Section: Generation Of Human and Mouse Dcs And Genementioning
confidence: 99%
“…While investigating the phenotypes of the resulting Th2 type cells, we observed that the Th2 effector CD4 T cells were poor IL-2 producers while acquiring the capacity to produce Th2 effector cytokines such as IL-4, IL-10, and IL-13 upon restimulation (supplemental materials). 4 In contrast, CD4 T cells stimulated without basophils or with IL-4-deficient basophils failed to produce Th2 cytokines but preserved IL-2-producing capacity (supplemental material). Given that IL-4, directly involved in Th2 differentiation, has long been known to suppress IL-2 production in activated T cells (9), these results prompted us to propose the hypothesis that IL-4 induces a factor that negatively control IL-2 production in activated CD4 T cells.…”
Section: Il-4-producing Th2 Type Cd4 T Cells Are Poor Il-2 Producersmentioning
confidence: 99%
“…In macrophages or LPS-stimulated monocytes, IL-4 was shown to inhibit the production of TNF-␣, IL-1␤, and IL-12 (1,2), and to suppress expression of Fc␥R and of metalloproteinase (2,3). IL-4 was also demonstrated to inhibit expression of L chain and NF-B activation in murine pre-B cells (4). In mast cells, IL-4 inhibited TNF-␣ production and FcRI expression (5,6).…”
mentioning
confidence: 99%